2012
DOI: 10.1111/j.1540-8183.2012.00737.x
|View full text |Cite
|
Sign up to set email alerts
|

Economic Modeling of New Stent Platforms to Evaluate Cost Effectiveness: Analysis of the TAXUS Liberté Versus TAXUS Express Stents

Abstract: This analysis confirms the utility of economic modeling in assessing new stent platforms. TAXUS Liberté 2.25 mm is economically dominant relative to TAXUS Express when treating small vessels. TAXUS Liberté Long is cost neutral to modestly more costly than TAXUS Express 2.25 mm from a payer perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…When inputs were varied by ±20%, results remained cost savings for Co‐Cr EES relative to BMS in all cases (not shown). Similarly, when base‐case inputs were varied using alternative values taken from published literature , all analyses showed that Co‐Cr EES was more effective and less costly versus BMS, with the exception of the cost of clopidogrel, which resulted in a cost of $9,755 per QALY gained (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When inputs were varied by ±20%, results remained cost savings for Co‐Cr EES relative to BMS in all cases (not shown). Similarly, when base‐case inputs were varied using alternative values taken from published literature , all analyses showed that Co‐Cr EES was more effective and less costly versus BMS, with the exception of the cost of clopidogrel, which resulted in a cost of $9,755 per QALY gained (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…One‐way sensitivity analyses were conducted in order to test the robustness of the base‐case analysis to alternative assumptions and data inputs related to transition probabilities, risks of events, resource use, DAPT therapy costs, and health utility (Table ) . A probabilistic sensitivity analysis (PSA) was conducted to simultaneously quantify the uncertainty in all key model input parameters.…”
Section: Methodsmentioning
confidence: 99%
“…Our study differs from existing decision‐analytic coronary stent model in several aspects. We derived the first year relative treatment effects from a cohort of CAD patients with a broad spectrum of clinical presentations in the real‐world practice.…”
Section: Discussionmentioning
confidence: 97%
“…The model consists of 2 parts: a short‐term element that simulates the clinical events of CAD patients within the first year and a long‐term element that projects the costs and effects from second to fifth year after index PCI (Figure ). The model is based on expert opinion and previously published models . The primary analysis builds on patient‐level clinical data, and incremental cost‐effectiveness ratio (ICER) is calculated for BP‐DES versus DP‐DES as the difference in 1‐year costs divided by the difference in quality‐adjusted life years (QALYs).…”
Section: Methodsmentioning
confidence: 99%
“…Long lesion length, particularly lesions requiring multiple overlapping stents, has been associated with an increased risk of periprocedural myocardial infarction (MI) . Using a single long stent to cover long lesions also appears to be more cost‐effective than using multiple shorter stents and may be associated with a reduced risk of adverse events compared with the use of multiple overlapping stents .…”
Section: Introductionmentioning
confidence: 99%